Studi Fenomenologi: Perspektif Perawat Mengenai Personal Hygiene Klien Di Instalasi Rawat Inap - rohni taufika sari (CNJ: Caring Nursing Journal, 2019)
Personal hygiene care for clients are common topic that are often discussed in nursing service. Numerous nurse assumptions emphasize that personal hygiene is essential for client, but in fact at the hospital especially inpatient care often faced by various obstacles which are effect on personal hygiene care for client. Generally, personal hygiene for hospitalized clients have less attention because it is not considered as a priority need and do not significant affect to client’s recovery. Nurse as a profession who has a body of knowledge clearly understand that personal hygiene care should to applied to all clients with any condition need, any age, and at any inpatient care unit. Therefore, is necessary to do exhaustive study how the nurse’s perspectives on personal hygiene care for client at inpatient care unit. This study used qualitative method with phenomenological approach. There were seven participants obtained by used purposive sampling technique. Data collection used by in-depth interview. There were three theme identified, namely purpose of personal hygiene care, principles of personal hygiene care and fundamental attitudes for nurses on personal hygiene care for client. The effectiveness of personal hygiene care for patients is cannot be separated from the nurse performance itself. The greatest support come from hospital manager by reminding all the nurses how important it is to take care of personal hygiene for clients, and providing facilities needed to improving quality of care.